Adherence to Urological Therapies for Lower Urinary Tract Symptoms Due to Benign Prostatic Enlargement During COVID-19 Lockdown - Morgia, Giuseppe; Lo Giudice, Arturo; Asmundo, Maria Giovanna; Rapallo, Ilenia; Carrino, Maurizio; Persico, Francesco; Terrone, Carlo; Malinaric, Rafaela; Tedde, Alessandro; Madonia, Massimo; Voce, Salvatore; Reale, Giulio; et al. (Frontiers in Urology, 2022)
Background: Due to the pandemic emergency secondary to COVID-19, many countries were forced to apply a variety of measures such as quarantine and total-nation-lockdown in order to contain the contagion. Medical adherence to chronic diseases may have been negatively influenced by restrictions due to COVID-19 pandemic. The purpose of this study is to investigate lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPE) patients’ adherence to urological therapies during COVID 19-lockdown period. Methods: In this cohort study we included a total of 151 male patients who had been prescribed medication for LUTS/BPE between January 2019 and December 2020. The prescriptive data of the following drugs were collected: alpha-blockers (AB), 5-alpha reductase inhibitors (5-ARI), 5-phosphodiesterase inhibitors (PDE5-i), anti-muscarinic, phytotherapy (i.e. serenoa repens). According to adherence or discontinuation of therapy, patients have been divided into two group; those who took their medication for a minimum of six months during the index period were considered into “Medical adherence group”; otherwise, the treatment was considered as “discontinued” if it was interrupted for a one-month period. Results: Overall, median age was 69.0 (interquartile range [IQR]: 63.0-74.0), median IPSS before lockdown was 15.0 (IQR: 11.0-18.0) and median IPSS-QoL before lockdown was 2.0 (IQR: 2.0-3.0). During lockdown, 19 patients (12.58%) stopped assumption of drugs due to pandemic situation and in particular, six (31.58%) stopped phytotherapy, two stopped AB + phytotherapy (10.53%), five stopped AB (26.32%), three stopped 5ARI (15.79%), one stopped antimuscarinic (5.26%) and two stopped other combination therapy (p<0.01). Among patients who stopped therapy, five (26.31%) reported a worsening of symptoms (score ≥ 3) while 14 (73.69%) did not (score < 3). During lockdown, five (3.31%) patients required hospitalization and in particular three (1.99%) for acute urinary retention and two (1.32%) for urinary tract infection. Conclusions: The rate of medical adherence for LUTS/BPE during COVID19 was 86.75% but 13.25% of patients interrupted drugs due to the pandemic situation. This rate has determined a slight increase of symptoms with potential impact on hospitalization. These results should be taken into account in order to build-up adequate strategies in telehealth to maintain medical adherence for chronic diseases.